Machine Learning-Based Evaluation on Craniodentofacial Morphological Harmony of Patients After Orthodontic Treatment - Wang, Xin; Zhao, Xiaoke; Song, Guangying; Niu, Jianwei; Xu, Tianmin (Frontiers in Physiology, 2022)
Objectives: Machine learning is increasingly being used in the medical field. Based on Machine learning models, the present study aims to improve the prediction performance of craniodentofacial morphological harmony judgement after orthodontic treatment and to determine the most significant factors. Methods: Dataset of 180 subjects were randomly selected from a large sample of 3706 finished orthodontic cases from six top orthodontic treatment centres around China. 13 algorithms were used to predict the value of cephalometric morphological harmony score of each subject and to search for the optimal model. Based on the feature importance ranking and by removing features, the regression models of Machine Learning (including the Adaboost, ExtraTree, and XGBoost and Linear regression model) were used to predict and compare the score of harmony for each subject from the dataset with cross-validations. By analysing the prediction values, the most optimal model and the most significant cephalometric characteristics was determined. Results: When 9 features were included, the performance of XGBoost regression model was MAE=0.267, RMSE=0.341, and Pearson correlation coefficient=0.683, which indicated that the XGBoost regression model exhibited the best fitting and predicting performance for craniodentofacial morphological harmony judgement. 9 cephalometric features including L1/NB (inclination of the lower central incisors), ANB (sagittal position between the maxilla and mandible), LL-EP (distance from the point of the prominence of the lower lip to the aesthetic plane), SN/OP (inclination of the occlusal plane), SNB (sagittal position of the mandible in relation to the cranial base), U1/SN (inclination of the upper incisors to the cranial base), L1-NB (protrusion of the lower central incisors), Ns-Prn-Pos (nasal protrusion) and U1/L1 (relationship between the protrusions of the upper and lower central incisors) were revealed to significantly influence the judgement. Conclusions: The application of XGBoost regression model enhanced the predictive ability regarding the craniodentofacial morphological harmony evaluation by experts after orthodontic treatment. Teeth position, teeth alignment, jaw position and soft tissue morphology would be the most significant factors influencing the judgement. The methodology also provided a guidance for application of machine learning models to resolve medical problems characterized by limited sample size.